Bedah Ulang Perbankan Konvensional Versus Perbankan Islam dalam Realitas Sosiologis - Nurfania, Andi Elvira; Gassing, Qadir; Rahman, Abd. (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This article discusses the conceptual differences and sociological realities between conventional banking and Islamic banking in Indonesia. Using a sociological economics approach, the study examines how both banking systems influence social behavior, public perceptions, and their implications for economic structures. The findings indicate that Islamic banking derives its legitimacy from the religious culture of society, while conventional banking gains legitimacy from economic modernization. Despite their differing principles, in social reality both systems experience convergence.